Analisis Motivasi dan Persepsi Kerja terhadap Pemilihan Karir Jabatan Fungsional Pengelola Barang Jasa dengan Minat sebagai Variabel Mediasi - Jatmiko Jatmiko; Kusuma Chandra Kirana Kirana; Samsul Hadi (IPM2KPE, 2024)
The aim of this research is to analyze the relationship between motivation and work perception on career choice in the functional position of goods and services manager, with interest as a mediating variable. This research was conducted using quantitative methods, with a population consisting of 257 State Civil Service Employees (ASN), and a sample of 157 respondents. The data analysis technique used was an inner model with the bootstrapping method. The research results show that work motivation and work perception have a positive influence on career choice. Apart from that, work motivation and work perception also have a positive effect on interest. Furthermore, interests have a direct and indirect influence on career choice. The conclusion is that work motivation and perception play an important role in choosing a career in the functional position of managing goods and services. Interest also mediates the relationship between work motivation and work perception and career choice. This shows the importance of understanding motivational factors and work perceptions in managing careers, as well as the role of interests in shaping individual career decisions in organizations. Keywords: Motivation, Interest, Job Perception, Career Choice